A Qualitative Study of Barriers to Enrollment into Free HIV Care: Perspectives of Never-in-Care HIV-Positive Patients and Providers in Rakai, Uganda. (22nd August 2013) - Nakigozi, Gertrude; Atuyambe, Lynn; Kamya, Moses; Makumbi, Fredrick E.; Chang, Larry W.; Nakyanjo, Neema; Kigozi, Godfrey; Nalugoda, Fred; Kiggundu, Valerian; Serwadda, David; Wawer, Maria; Gray, Ronald
Abstract : Background . Early entry into HIV care is low in Sub-Saharan Africa. In Rakai, about a third (31.5%) of HIV-positive clients who knew their serostatus did not enroll into free care services. This qualitative study explored barriers to entry into care from HIV-positive clients who had never enrolled in care and HIV care providers. Methods . We conducted 48 in-depth interviews among HIV-infected individuals aged 15–49 years, who had not entered care within six months of result receipt and referral for free care. Key-informant interviews were conducted with 12 providers. Interviews were audio-recorded and transcripts subjected to thematic content analysis based on the health belief model. Results . Barriers to using HIV care included fear of stigma and HIV disclosure, women's lack of support from male partners, demanding work schedules, and high transport costs. Programmatic barriers included fear of antiretroviral drug side effects, long waiting and travel times, and inadequate staff respect for patients. Denial of HIV status, belief in spiritual healing, and absence of AIDS symptoms were also barriers. Conclusion . Targeted interventions to combat stigma, strengthen couple counseling and health education programs, address gender inequalities, and implement patient-friendly and flexible clinic service hours are needed to address barriers to HIV care.